Descriptive and subject cataloguing : a workbook - Raju, Jaya Dr.; Raju, Reggie; ScienceDirect eBooks (Oxford [England] : Chandos Publishing, 2006)
A workbook on descriptive and subject cataloguing featuring practical examples and suggested solutions to reinforce theoretical concepts and practical application in descriptive cataloguing (using Anglo-American Cataloguing Rules, 2nd ed., 1998 rev.), bibliographic classification (using Dewey Decimal Classification, 21st ed.) and assigning subject headings (using Sears List of Subject Headings, 17th ed.).
Introduction -- Theoretical principles of information organization: an overview -- Examples for cataloguing, classification and assigning subject headings --Suggested solutions -- Conclusion.
Includes bibliographical references.
Elsevier
Keywords: Descriptive cataloguing; Descriptive cataloguing -- Problems, exercises, etc; Subject cataloguing; Subject cataloguing -- Problems, exercises, etc; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Electronic books